2019
DOI: 10.3390/w11112302
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Coagulation with Mn(III) Pre-Oxidation for Treatment of Micro-Polluted Raw Water

Abstract: Mn(III) oxidation technology has attracted increasing interest in recent years because of its fast decontamination kinetics and second-pollution-free characteristic. Whether it can be used as a pre-oxidation step to enhance conventional coagulation process remains to be evaluated. Herein, an Fe-coagulation/sedimentation process combined with Mn(III) pre-oxidation (Mn(III)+C/S), hypochlorite pre-oxidation (Cl2+C/S), and permanganate pre-oxidation (PM+C/S) was applied to treat simulated micro-polluted raw water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The optimum alum dosage (A o ) obtained from the procedure in the previous section was taken as the maximum dosage in experiments to determine the optimum combination of chlorine dioxide and alum. The rationale for this, is that the addition of a pre-oxidising agent should result in reduction of alum dosage since most organics and algae are expected to have been oxidised by the oxidant resulting in less alum required for coagulation (Yan et al 2019). Typical doses for pre-oxidation with chlorine dioxide range from 0.07 to 2 mg/L (Shams et al 2011).…”
Section: Experimental Designmentioning
confidence: 99%
“…The optimum alum dosage (A o ) obtained from the procedure in the previous section was taken as the maximum dosage in experiments to determine the optimum combination of chlorine dioxide and alum. The rationale for this, is that the addition of a pre-oxidising agent should result in reduction of alum dosage since most organics and algae are expected to have been oxidised by the oxidant resulting in less alum required for coagulation (Yan et al 2019). Typical doses for pre-oxidation with chlorine dioxide range from 0.07 to 2 mg/L (Shams et al 2011).…”
Section: Experimental Designmentioning
confidence: 99%
“…Chlorine dioxide pretreatment, like chlorine, has a positive effect on algae removal. 67 Lin 68 found that ClO 2 dosing had a strongest ability to lower algae viability and oxidize ionic and complexed soluble Mn. Shi 69 found that the optimal dose of 0.5 mg L À1 of Cl 2 could prevent the outbreak of Pseudomonas aeruginosa.…”
Section: Chlorine and Chlorine Dioxidementioning
confidence: 99%
“…It is often reported that Mn 3+ oxidation technology is used as peroxidation step to strengthen the traditional coagulation process. Yan, Sun, et al (2019), Yan, Yuan, et al (2019) reported the treatment of simulated micro-polluted raw water by iron coagulation and sedimentation process combined with Mn 3+ peroxidation (Mn 3+ -C/S), hypochlorite peroxidation, and permanganate peroxidation. The target EPs includes acesulfame, carbamazepine, bisphenol S, and nano-ZnO.…”
Section: Coagulationmentioning
confidence: 99%
“…In general, the chemical oxidation processes are used to degrade the EPs into the biodegradable intermediate. Then, further oxidation is carried out by biological method to improve the mineralization rate of EPs and the quality of effluent (Monteil et al, 2019; Wang, Ying, et al, 2019; Wang, Su, et al, 2019; Wang, Wang, et al, 2019; Wang, Huang, et al, 2019; Wang, Cai, et al, 2019; Wang, Zhu, et al, 2019; Wang, Yin, et al, 2019; Wang, Qian, et al, 2019; Wang, Zhang, et al, 2019; Yan, Sun, et al, 2019; Yan, Yuan, et al, 2019). The combination of various chemical oxidation methods can improve the production efficiency of active groups in the system, leading to the removal rate improvement of EPs (Chen, Zhu, et al, 2019; Chen, Zhang, et al, 2019; Figueredo, Rodríguez, Checa, & Beltran, 2019; Orimolade, Koiki, Peleyeju, & Arotiba, 2019; Sedlazeck et al, 2019; Wang, Ying, et al (2019); ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; Wang, Su, et al (2019), Wang, Wang, et al (2019), Wang, Huang, et al (2019), Wang, Cai, et al (2019), Wang, Zhu, et al (2019), Wang, Yin, et al (2019), Wang, Qian, et al (2019), Wang, Zhang, et al (2019); Xu, Yang, et al, 2019; Xu, Zhao, et al, 2019).…”
Section: Combinations Of Treatment Technologiesmentioning
confidence: 99%